Effects of the Current Japanese Guideline for Dedicated, Intensive Lipid-lowering Therapy on Lipid Profile and Coronary Events in Patients After Acute Coronary Syndrome. (2022) - Yamada, Ryotaro; Kume, Teruyoshi; Okamoto, Hiroshi; Yamashita, Masahiro; Koto, Satoshi; Kamisaka, Kyo; Sasahira, Yoshitaka; Sudo, Yasuyuki; Enzan, Ayano; Tamada, Tomoko; Koyama, Terumasa; Imai, Koichiro; et al.
No abstract available